TNF-alpha and insulin-resistance: metabolic effects of in vivo therapeutic blockade - F. Ursini (PAGEPress Publications, 2011)
Insulin resistance is a key pathophysiologic feature of obesity, type 2 diabetes mellitus and prediabetic states (impaired fasting glucose, impaired glucose tolerance). TNF-α, a proinflammatory cytokine, plays an important role in the pathogenesis of insulin resistance associated with inflammation during the course of rheumatic diseases. Therapies aimed at neutralizing TNF-α, such as the monoclonal antibody infliximab, represent a relatively new approach in the treatment of rheumatic diseases and allow to obtain significant results in terms of control of the inflammatory process. In this article we reviewed the scientific evidence published in the literature about a potential role of TNF-α blockade in improving insulin resistance in rheumatic patients without diabetes.